2021
DOI: 10.3390/antibiotics10050556
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacology of Bacteriophage Therapy: A Focus on Multidrug-Resistant Pseudomonas aeruginosa Infections

Abstract: Pseudomonas aeruginosa is one of the most common causes of healthcare-associated diseases and is among the top three priority pathogens listed by the World Health Organization (WHO). This Gram-negative pathogen is especially difficult to eradicate because it displays high intrinsic and acquired resistance to many antibiotics. In addition, growing concerns regarding the scarcity of antibiotics against multidrug-resistant (MDR) and extensively drug-resistant (XDR) P. aeruginosa infections necessitate alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 163 publications
0
7
0
Order By: Relevance
“…In many lytic phages, host lysis is achieved by singlegene lyses protein or through the holin-endolysin system (Attama et al, 2017). Phages can also produce enzymes when biofilms are present to dissolve the biofilm matrix produced by P. aeruginosa (Holger et al, 2021). Gupta and Prasad (2011) successfully purified an endolysin from phage P-27/HP and showed its ability (about 99.9%) to decolonize the spleens of treated mice from S. aureus 27/HP.…”
Section: Resultsmentioning
confidence: 99%
“…In many lytic phages, host lysis is achieved by singlegene lyses protein or through the holin-endolysin system (Attama et al, 2017). Phages can also produce enzymes when biofilms are present to dissolve the biofilm matrix produced by P. aeruginosa (Holger et al, 2021). Gupta and Prasad (2011) successfully purified an endolysin from phage P-27/HP and showed its ability (about 99.9%) to decolonize the spleens of treated mice from S. aureus 27/HP.…”
Section: Resultsmentioning
confidence: 99%
“…Through expanding Pyocyanin concentration from 50 mg/ml to 100 mg/ml, the antimicrobial activity is improved and enhanced; therefore the pyocyanin is concentration dependent as an antibiotic activity. Synergistic activity showed that antibacterial activity of Standard Pyocyanin in combination with antibiotics on Multidrug resistant isolates were increased and enhanced on tested bacteria inhibited growth It's possible that in Figure (9) for S. aureus, pyocyanin increased the activity of gentamicin's binding to the 16s rRNA at the 30s ribosomal subunit, interfering with the translation of mRNA and, as a result, causing the creation of truncated or ineffective proteins. [25].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of multidrug-resistant (MDR) and extensively drug-resistant (XDR) germs, as well as the most severe patients. [9] & [10]. Pseudomonas aeruginosa is difficult due to the bacteria's inherent capacity to acquire antibiotic resistance, form impenetrable biofilms, and release a huge variety of virulence factors.…”
Section: Introductionmentioning
confidence: 99%
“…This tool has been extensively used to evaluate viability in bacteria 19 , but, to our knowledge, never to monitor killing by phages. Here, we show this application on Pseudomonas aeruginosa and Klebsiella pneumoniae , two ESKAPE pathogens against which phage therapy is particularly relevant 20 , 21 . We demonstrate that the developed assay correlates with standard assays, such as plaque assays and bacterial viability on plate, and propose a way of optimizing the method for phage screening in a clinical setting.…”
mentioning
confidence: 95%